AN ANALYZE OF THE CORRESPONDENCE LEVELS BETWEEN TURKISH READING PROFICIENCY OBJECTIVES AND THE PISA SCALE - Zekerya BATUR (Fırat University, 2019)
The aim of this study is to present to what extent the teaching programs in Turkey can promote the skills which have been measured in PISA applications. For this purpose, the question “do the reading comprehension objectives in the 6th – 8th grade Turkish teaching program overlap the proficiency levels defined in PISA test?” is tried to be answered. This study is descriptive and it is based on document analysis. In the study, the summary definitions of the “2009 PISA Reading Proficiency Levels” of and “Turkish Course Reading Proficiency Objectives” are reviewed and compared. According to the research, 18 of the 51 objectives of 2006 Primary (6th, 7th, 8th grade) Turkish Reading Proficiency Objectives are observed to overlap the PISA’s low level objectives. The fact that Turkish reading proficiency objectives’ mostly overlapping to the low-level objectives of PISA is remarkable here. In parallel with this, it has been always a problem to advance students to the up next level. It is also seen that, the objectives planned for the Turkish courses are thought to be usually composed that of 3rd, 4th and 5th grade levels. Therefore, it seems hardly possible for the 6th, 7th, and 8th grade students to advance to the next cognitive levels. According to those low-level objectives, it can be said that the students remain at the literacy level. In this sense, when compared to the PISA proficiency levels, the Turkish course objectives are too superficial and also their implementation levels are relative. Hence, the Turkish course objectives should be changed into more measurable, concrete and applicable state and they should be enhanced to the PISA level.